Mycoplasma pneumoniae-associated diffuse alveolar haemorrhage: an atypical presentation of a prevalent pathogen. Issue 4 (29th April 2022) - Slauer, Ryan D; Mourad, Ahmad; Krishnan, Govind; Feeney, Colby
Abstract : A transgender man in his late teens presented with signs of multisystem disease, including hepatitis, mucositis and bone marrow suppression. He later developed dyspnoea, leucocytosis and bilateral pulmonary infiltrates on chest radiograph. He was treated for community-acquired pneumonia. After several days of treatment, he developed hypoxaemic respiratory failure due to bronchoscopy-confirmed diffuse alveolar haemorrhage (DAH). The differential diagnosis and workup were extensive, and he was ultimately treated with intravenous steroids and five sessions of plasmapheresis for a presumed autoimmune aetiology. Investigations were remarkable only for elevated IgM and IgG to Mycoplasma pneumoniae (MP). This case represents a rare presentation of multisystem disease secondary to MP in adults. Clinicians should consider Mycoplasma infection in cases of multisystem disease and observe for DAH even after initiation of appropriate therapy.